Analysis of Public Relations Program in Building School Branding (Multisite Study at SMP IT Harapan Mulia Palembang and SMP IT Al Furqon Palembang) - Santoso, Imam; Eko Pramono, Suwito; Yusuf, Amin (Educational Management, 2021)
School public relations is one of the school's management functions in the field of public relations. It is supposed to act as a bridge between the organization and its constituents, establishing communication and sustaining positive relationships. The purpose of this study is to examine the school's public relations program for the purpose of developing school branding. This study used a qualitative approach, employing a case study design with multiple sites. Principals, school public relations, and PPDB members are the main data sources. Techniques for data collection was observation, interviewing, and documentation. Data analysis is a technique that entails data reduction, data display, and conclusion drawing. The result was: The public relations program activities of SMP IT Harapan Mulia Palembang are as follows: 1) develop school logos and uniforms, 2) develop taglines, 4) develop a charactersitic and outstanding program, and 6) pursue successes. Communication; 1) establish social media platforms such as facebook, whatsapp, youtube, and instagram; 2) establish corporate partnerships; 3) establish calendars; 4) establish press relations; and 5) organize family meetings. And the activities of the public relations program at SMP IT AL Furqon Palembang: 1) developed superior programs for full-day and boarding school programs, 2) created slogans for thinkers, dhikr experts, and endeavor experts. 3) Designing school logos and uniforms; 4) establishing special programs; and 5) recruiting qualified and competent educators. Additional communication includes the following: 1) leveraging social media platforms such as Instagram, Facebook, Whatsapp, and YouTube. 2) develop a school website; 3) form corporate relationships; 4) meeting with parents; and 5) meeting with the local community. It can be stated that the school public relations program is highly effective at developing school branding, even though various obstacles exist in its implementation.